Charge and thermoelectric transport in polymer-sorted semiconducting single-walled carbon nanotube networks - Statz, Martin; Schneider, Severin; Berger, Felix J.; Lai, Lianglun; Wood, William A.; Abdi-Jalebi, Mojtaba; Leingang, Simone; Himmel, Hans-Jörg; Zaumseil, Jana; Sirringhaus, Henning (ACS nano, 2020)
Understanding the charge transport mechanisms in chirality-selected single-walled carbon nanotube (SWCNT) networks and the influence of network parameters is essential for further advances of their optoelectronic and thermoelectric applications. Here, we report on charge density and temperature-dependent field-effect mobility and on-chip field-effect-modulated Seebeck coefficient measurements of polymer-sorted monochiral small-diameter (6,5) (0.76 nm) and mixed large-diameter SWCNT (1.17-1.55 nm) networks (plasma torch nanotubes, RN) with different network densities and length distributions. All untreated networks display balanced ambipolar transport and electron-hole symmetric Seebeck coefficients. We show that charge and thermoelectric transport in SWCNT networks can be modeled by the Boltzmann transport formalism, incorporating transport in heterogeneous media and fluctuation-induced tunneling. Considering the diameter-dependent one-dimensional density of states (DoS) of the SWCNTs composing the network, we can simulate the charge density and temperature-dependent Seebeck coefficients. Our simulations suggest that scattering in these networks cannot be described as simple one-dimensional acoustic and optical phonon scattering as for single SWCNTs. Instead the relaxation time is inversely proportional to energy (τ ∝ (E - EC)s, s = −1, EC being the energy of the first van Hove singularity), presumably pointing toward the more two-dimensional character of scattering events and the necessity to include scattering at the SWCNT junctions. Finally, our observation of higher power factors in trap-free, 1,2,4,5-tetrakis(tetramethylguanidino)benzene-treated (6,5) networks than in the RN networks emphasizes the importance of chirality selection to tune the width of the DoS. To benefit from both higher intrinsic mobilities and a large thermally accessible DoS, we propose trap-free, narrow DoS distribution, large-diameter SWCNT networks for both electronic and thermoelectric applications.
Gesehen am 02.04.2022